APPLICABILITY OF ARTICLE 170-A OF THE NATIONAL TAX CODE (CTN) TO TAX UNDUE PAYMENTS ARISING FROM UNCONSTITUTIONALITY (CIPEEX, 2025)
This paper examines the applicability of Article 170-A of Brazil’s National Tax Code (CTN) to undue tax payments arising from unconstitutional statutes and adopts a doctrinal approach combined with case-law analysis. It aims to determine whether, and to what extent, the prohibition of set-off before res judicata applies when the undue payment results from an assessment grounded on an unconstitutional law, distinguishing the effects on judicial refund and administrative set-off. The method consists of a literature review and a survey of superior court precedents, focusing on the ratio decidendi and practical consequences for taxpayers and the Treasury. The findings indicate that prevailing case law extends Article 170-A to cases of undue payments due to unconstitutionality, conditioning set-off on the final and unappealable judgment that recognizes the tax’s unenforceability, while not barring refund (repetição de indébito) after a definitive decision and subject to statutory procedures. It concludes that applying Article 170-A in these scenarios promotes legal certainty and fiscal balance, ensuring recovery of unduly paid amounts either by refund or set-off, in accordance with legal requirements and limitation periods.
Keywords: tax undue payment; unconstitutionality; Article 170-A of the National Tax Code; tax set-off